The Crucible of War, 1939-1945 The Official History of the Royal Canadian Air Force - Greenhous, Brereton; Harris, Steven J.; Johnston, William C (Heritage, 2019)
Some 40 per cent of RCAF aircrew who served overseas during the Second World War did so in RACF squadrons. This is their story. The first RCAF squadron to see action in the Second World War was No. 1 Fighter Squadron, later to be No. 401, which from 18 August 1940 participated in the Battle of Britain. The last, in a still active theatre, were Nos. 435 and 436, delivering supplies in Burma until late August 1945. In between, RCAF squadrons served in all the major commands and in most major theatres of war. They were engaged by day and by night in air-to-air combat, strategic bombing, photo-reconnaissance, anti-shipping strikes and anti-submarine patrols, close air support, interdiction, and tactical airlift supply. The Crucible of War is divded into five parts: Air Policy, the Fighter War, the Maritime Air War, the Bomber Air War, and the Air Transport War.